Central bank measures in support of the financial sector in the EU and the United States - Stéphanie Marie Stolz; Michael Wedow (Intereconomics, 2010)
The extensive public sector measures in support of the fi nancial sector have been key to managing the fi nancial crisis that erupted in mid-2007 and intensified after the bankruptcy of Lehman Brothers. This article looks into the measures taken by central banks to contain the impact of the crisis. This article reviews and compares the measures adopted by the Eurosystem, the Bank of England (BoE) and the Federal Reserve System (Fed). A complementary article, to appear in a subsequent issue, will deal with governments' responses to the crisis.
Keywords: 330